„You are the Father of All Things, Guardian of Your Sons” : (According to Zviad Gamsakhurdia Poetry) - Shengelia, Ketevan (Actual Problems of Kartvelology, 2019)
The introduction of the speech is dedicated to a general discussion of the personality of Zviad Gamsakhurdia. Later he is presented as a poet and a writer. Is shown thematic priorities of Zviad Gamsakhurdia and the aspects, where the author perceives religious theme and the theme of homeland as an inseparable one; these motives are of prior importance in his poetry. There are some specific group of poems that are dedications to some people or events and the poems - revealing the sentiments; coverage of two themes simultaneously is also observed. His philosophical and world view credos are discussed as well; are stated his extended interest towards the world literature. Zviad Gamsakhurdia’s translations of poetry are also observed. The present work covers a personal attitude of Zviad Gamsakhurdia towards the methods of research of literature. Poet’s attitude towards mythology is also shown. When discussing poetry of Zviad Gamsakhurdia, we pay attention to the rhythm and ntersyllabic pauses, where the different forms of rhyme and rhythm are detected. There is no poetry without an artistic images and creative thinking. In this respect, poetic images and the original way of presenting the problems in Zviad Gamsakhurdia works, invite special interest. This theme is thoroughly covered in the presented work. Historicism, myths, antic space, outstanding orthodox thinking,vivification of geographical objects and partial rationalization of a poetic world, unveiling the cognitive values and philosophical aspects are characteristic features of Zviad Gamsakhurdia poetry. Literary language is a main leverage for each creative worker. Today academism is out of “fashion” among some, so called “writers,” which will bring some undesirable problems into the cultural sphere. In this respect, literary language and poetry of Zviad Gamsazurdia also calls for a special attention. He is free from the threat of being infected by barbarisms and scabrousness; his style is refined and simple. These very topics will be covered in the conclusion of the given speech.